Treatment with cyclosporin and risks of graft rejection in male kidney and heart transplant recipients with non-O blood. Issue 6653 (8th October 1988) - Hendriks, G. F.; van Steenberge, E. P.; Schreuder, G. M.; Wenting, G. J.; Mochtar, B.; Bos, E.; Simoons, M. L.; Balk, A. H.; Laird-Meeter, K.; Essed, C. E.
Abstract : In a consecutive series of 146 kidney transplant recipients treated with cyclosporin A a strong correlation between matching for the HLA-A, HLA-B, and HLA-DR loci specificities and outcome of the grafts was observed in male recipients with non-O blood groups. Such a beneficial effect of matching was not found in female patients or male patients with blood group O. In these patients survival of the grafts at one year was good irrespective of the number of HLA-A, B, and DR mismatches. Also in 47 male heart transplant recipients immune responsiveness against mismatched HLA antigens was related to blood group. A significantly higher incidence of rejection episodes was observed in male patients with non-O blood groups (n = 32) than in those with blood group O (n = 15). Matching for HLA-DR reduced the number of acute rejection episodes in male patients with non-O blood. These findings may help explain the controversial reports about the importance of HLA matching in organ transplantation. Furthermore, as most candidates for heart transplantation are male and not of blood group O, the higher incidence of graft rejection in these patients underscores the need for an exchange strategy of donor hearts.